Impacts of Beel Sanctuary Management Project on Fish Production and Socio -Economic Competence: a Study in the HaltiBeelTanki Fish Sanctuary (Journal of Environmental Science and Natural Resources, 2018)
The research was conducted to find out the impacts of Beel sanctuary management on fish production of the HaltiBeelTanki fish sanctuary and socio-economic competence of adjacent fishermen, Natore, Bangladesh through random sampling with questionnaire survey and secondary data. The main objectives of the research were- to find out the present status of fish production of the Beel and to know the socio-economic condition of the surrounding fishermen. A total of 68 fishermen were selected and interviewed. In the studied Beel the annual fish production was 8.8 MT in 2012 where Beel sanctuary management increased the production up to 15.2 MT in 2013. The average fish production increased 2.6 MT per year. Fish species such as Ayre, Calbaosh, Pabda, Sharputi etc. were absent before the project (before 2012) but at present available at a rate of 20g, 1000g, 300g, and 1200g per day respectively. The study revealed that about 77% of the fishermen preferred nuclear family where only 23% joint family. It was found that about 63% fishermen were illiterate and there was no H.S.C pass fisherman. The average income of the selected fishermen was 8125 taka/month and about 58% fishers were able to save money 501-1000 taka/month after the project.J. Environ. Sci. & Natural Resources, 10(2): 55-63 2017